IDENTIFIKASI SENYAWA ALKALOID EKSTRAK ETANOL 70% DAUN BELIMBING MANIS (Averhoa carambola L.) SECARA KROMATOGRAFI LAPIS TIPIS DENGAN ELUEN N-HEKSAN DAN ETIL ASETAT - Gigih Kenanga Sari; Nazdia Putri Nur Afiana (Jurnal Farmasi IKIFA, 2024)
This research aims to identify alkaloid compounds from 70% ethanol extract of sweet starfruit leaves (Averhoa carambola L.) originating from Tarub Village, Tawangharjo District, Grobogan Regency. The identification method is laboratory observation using Thin Layer Chromatography (TLC) using the eluent N-hexane and ethyl acetate ratio (7:3). The selection of N-hexane and ethyl acetate eluents based on different polarities aims to obtain the best solvent, which can have an influence on the chemical content produced. The solvent was also able to influence the yield of the resulting compound. The TLC results with N-hexane eluent showed an orange red color and an Rf value of 0.8. And the TLC results with ethyl acetate eluent showed a pink color with an Rf value of 0.2. Conclusion: 70% ethanol extract of sweet star fruit leaves positively contains alkaloid compounds.